Systemic Concocting of Cross‐Linked Enzyme Aggregates of Candida antarctica Lipase B (Novozyme 435) for the Biomanufacturing of Rhamnolipids. Issue 3 (26th February 2019) - Rathankumar, Abiram Karanam; SaiLavanyaa, Sundar; Saikia, Kongkona; Gururajan, Anusha; Sivanesan, Subramanian; Gosselin, Mathilde; Vaidyanathan, Vinoth Kumar; Cabana, Hubert
Abstract: In the present study, Candida antarctica lipase B was immobilized on amine‐functionalized silica microspheres as cross‐linked enzyme aggregates (CLEA) and utilized for the biomanufacturing of rhamnolipids (RL). Lipase CLEA synthesized under optimized conditions of 2.0:1.0 by volume of silica microsphere/enzyme concentration, a 1.0:2.5 (v/v) ratio of enzyme/2‐propanol, 7 mM glutaraldehyde concentration, when incubated at pH 9.0 and 40 °C, for a cross‐linking time of 30 min were observed to exhibit superior biocatalytic properties and a maximum enzyme load of 770 U g −1 . Lipase CLEA exhibited enhanced pH stability in acidic and alkaline media and increased temperature resistance as compared to free lipase. Both free and CLEA lipases were used to synthesize RL in different solvent systems. After 12 h, from initiation of the esterification, the degree of esterification (molar conversion yield) reached 46% and 71% in the batch mode. 1 H and 13 C nuclear magnetic resonance (NMR) and high‐performance liquid chromatographic (HPLC) analysis confirm RL production by CLEA lipase. The CLEA showed greater confrontation to enzyme‐mediated bioprocess approach as compared to its soluble counterpart and exhibited excellent RL production and catalytic activity even after its tenth successive reuse. Abstract :